An Unusual Presentation of Metastatic Colon Adenocarcinoma in the Oral Cavity - Abhilash Bhaskaran; Sam Harding; David Courtney (Case Reports in Dentistry)
Background. A case report of a nonhealing ulcer of the tongue histologically proven to be adenocarcinoma. Method. A 92-year-old man underwent clinical, immunochemistry, and imaging investigation. Results. Tests confirmed a distant metastasis of a primary colorectal carcinoma. Conclusion. Metastasis from colorectal carcinoma to the oral cavity is primarily to bone, but non-healing ulcers of the oral cavity should be considered in differential diagnoses.